A Cell‐Based Assay Reveals Nuclear Translocation of Intracellular Domains Released by SPPL Proteases. (6th May 2015) - Mentrup, Torben; Häsler, Robert; Fluhrer, Regina; Saftig, Paul; Schröder, Bernd
<x xml:space="preserve">Abstract</x> During regulated intramembrane proteolysis (RIP) a membrane‐spanning substrate protein is cleaved by an ectodomain sheddase and an intramembrane cleaving protease. A cytoplasmic intracellular domain (ICD) is liberated, which can migrate to the nucleus thereby influencing transcriptional regulation. Signal peptide peptidase‐like (SPPL) 2a and 2b have been implicated in RIP of type II transmembrane proteins. Even though SPPL2a might represent a potential pharmacological target for treatment of B‐cell‐mediated autoimmunity, no specific and potent inhibitors for this enzyme are currently available. We report here on the first quantitative cell‐based assay for measurement of SPPL2a/b activity. Demonstrating the failure of standard Gal4/VP16 reporter assays for SPPL2a/b analysis, we have devised a novel system employing β‐galactosidase (βGal) complementation. This is based on detecting nuclear translocation of the proteolytically released substrate ICDs, which results in specific restoration of βGal activity. Utilizing this potentially high‐throughput compatible new setup, we demonstrate nuclear translocation of the ICDs from integral membrane protein 2B (ITM2B), tumor necrosis factor (TNF) and CD74 and identify secreted frizzled‐related protein 2 (SFRP2) as potential transcriptional downstream target of the CD74 ICD. We show that the presented assay is easily adaptable to other intramembrane proteases and therefore represents a valuable tool for the functional analysis and development of new inhibitors of this class of enzymes. <inline-graphic xlink:href="ark:/27927/pgj1m9qb41c" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />